Inner valence excitations of condensed neon - Kassühlke*, B.; Feulner, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Applying two-dimensional electron spectroscopy, we investigate bound and continuum excitations of neon films condensed onto clean metal surfaces, in the energy range of the [Ne 2s] singly and [Ne 2p2] doubly excited states. Precise energy values of excitons and ionization potentials are obtained for the surface and for the bulk, and compared to data for the isolated neon atom. In addition, valuable information on the mobility and the decay of excitons in this energy range is accessible with our technique.